CARACTERISTICAS CLINICAS ENDOSCOPICAS Y ANATOPATOLOGICAS DEL ADENOCARCINOMA GASTRICO - Gutiérrez Manay, Juan (1999)
Gastric cancer in our country ocupies first place in men and second in woman. The purpose of this works was to know in Dos de Mayo Hospital some varieties of epidemiological gastric cancer of 100 patients 25 were chosen to cumply endodoscopy and anatopatology descement. The big gest group corresponds between 51 to 80 years with 68% of male, with a 56% of the place of procedence. The time of sickneess correspon ding between 56%. The frequent symthon was abdominal pain, (84%); patiens (68%); loose of weight (68%). Endoscopy was efective with 88%. The localization of the tumours was the cave with a 48%. There was no significant difference to the Bormann class being lightly great Class III with 32%. In this study of 25 patients gastric cancer was more frequent inmale between 1 month 1 year; with characteristies of abdominal pain, paleness and loose of wight.